Peningkatkan Kemampuan Seni AUD Melalui Teknik Kolase Berbasis Kearifan Lokal Kota Palembang - Firabeliya, Nanda Audry; Dezyemita, Tarsya Rahma; Pasha, Aulia Shafira; Arista, Sindy Agustina; Kania, Refi; Jannah, Adinda Mutiara; Pagarwati, Lia Dwi Ayu; Zulaiha, Dara (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2024)
Art development is one aspect that needs to be paid attention to from an early age. Because art can be used as a forum for children to express their imagination and self-expression. The aim of this research is to obtain information on the use of collage techniques to improve children's artistic abilities at Kartika II-I Kindergarten. The research uses classroom action with the implementation stages adopting the Kemmis & Tagart model including 1) planning, 2) implementation, 3) observation and 4) reflection. The implementation of this model was carried out in 2 cycles, with 2 meetings in each cycle. The research subjects were 16 children aged 4-5 years at Kartika II-I Kindergarten. Researchers in collecting data used interview and observation techniques. After the data is obtained, it will be analyzed using qualitative and quantitative data analysis techniques. The research results obtained a score in pre-action of 56.5 and after action in cycle 1 of 68.1 and cycle 2 of 78.3. Thus, the researchers concluded that using collage techniques can improve children's artistic abilities.